2003
DOI: 10.1007/s10237-002-0021-0
|View full text |Cite
|
Sign up to set email alerts
|

Complex distributions of residual stress and strain in the mouse left ventricle: experimental and theoretical models

Abstract: Most soft biological tissues, including ventricular myocardium, are not stress free when all external loads are removed. Residual stress has implications for mechanical performance of the heart, and may be an indicator of patterns of regional growth and remodeling. Cross-sectional rings of arrested ventricles opened up when a radial cut was made (initial mean opening angles were 64 +/- 17 degrees), but further circumferential cuts revealed the presence of additional residual stresses in the tissue with further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 29 publications
(44 reference statements)
5
31
0
Order By: Relevance
“…However, the structures of the two layers were similar with more elastin and less collagen found in the endocardial layers (see Figs. 1-3), consistent with the more extensive opening angles found with endocardial sections than with epicardial sections by Omens et al (24), which we confirmed in this study (data not shown). Thus, the endocardial layer of elastin may also contribute to the net residual strain of the myocardium; however, we were not able to confirm this directly due to the inability to dissect this layer free from the wall.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…However, the structures of the two layers were similar with more elastin and less collagen found in the endocardial layers (see Figs. 1-3), consistent with the more extensive opening angles found with endocardial sections than with epicardial sections by Omens et al (24), which we confirmed in this study (data not shown). Thus, the endocardial layer of elastin may also contribute to the net residual strain of the myocardium; however, we were not able to confirm this directly due to the inability to dissect this layer free from the wall.…”
Section: Discussionsupporting
confidence: 95%
“…However, our results clearly demonstrate that the VP has a significant impact on the opening angle and, therefore, must make a major contribution to the residual stress of the LV. The increased opening angles found in epicardial portions of myocardium slices are consistent with the VP being an important factor in the residual stress found in the resting heart (24). This concept is also supported by the report by Omens et al (25), which showed that the opening angle does not change during pressure overload despite significant cardiomyocyte hypertrophy.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…They argued that myocardial laminae may be the principal residualstress-bearing structures in the LV. A recent experimental and theoretical study by Omens, McCulloch and Criscione (2003), on cross-sectional rings of arrested mouse ventricles showed that further stress is relieved by making a circumferential cut after the radial cut. The cutting experiments were analyzed by a cylindrical shell model with incompressible hyperelastic material properties.…”
Section: Residual Stress Growth and Remodelingmentioning
confidence: 99%
“…Generally, residual strain/stress in anisotropic hyper elastic conduit, such as classical tubes, some specific prosthetic devices and arteries, can be characterized by the opening angle H 0 of the sector-like cross-section. This phenomenon has been known in arterial wall for at least 40 years and residual strain/stress has implication not only for stress gradients such as in classical conduit (elastomeric), but also for growth and remodeling in the living tissue (Huang et al, 1998;Omens et al, 2003). In addition to their ability to homogenize the stress field in the arterial wall, residual strains make arteries more compliant and thereby improve their performance as elastic reservoirs and ensure more effective local control of the arterial lumen by smooth muscle cells.…”
Section: Introductionmentioning
confidence: 99%